2014
DOI: 10.1002/ece3.941
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling community functional components in a litter‐macrodetritivore model system reveals the predominance of the mass ratio hypothesis

Abstract: Recent investigations have shown that two components of community trait composition are important for key ecosystem processes: (i) the community-weighted mean trait value (CWM), related to the mass ratio hypothesis and dominant trait values in the community, and (ii) functional diversity (FD), related to the complementarity hypothesis and the divergence of trait values. However, no experiments controlling for the inherent dependence between CWM and FD have been conducted so far. We used a novel experimental fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 46 publications
7
32
0
Order By: Relevance
“…Bílá et al () concluded that dominant trait values in the community play a chief role in driving ecosystem processes such as C cycling processes (so corroborating the mass ratio hypothesis); it is yet to be determined whether the generality of their findings also hold true for other ecosystem processes. Here, we find that ecosystem engineers like our two earthworm species indeed possess dominant trait values concerning emissions of N 2 O and CO 2 .…”
Section: Discussionmentioning
confidence: 98%
“…Bílá et al () concluded that dominant trait values in the community play a chief role in driving ecosystem processes such as C cycling processes (so corroborating the mass ratio hypothesis); it is yet to be determined whether the generality of their findings also hold true for other ecosystem processes. Here, we find that ecosystem engineers like our two earthworm species indeed possess dominant trait values concerning emissions of N 2 O and CO 2 .…”
Section: Discussionmentioning
confidence: 98%
“…These studies found opposite results (Gartner & Cardon, ; Gessner et al., ; Hättenschwiler, Tiunov, & Scheu, ), depending on abiotic conditions (Jonsson & Wardle, ; Santonja, Fernandez, Gauquelin, & Baldy, ), composition and functional properties of mixed litter (Barantal, Schimann, Fromin, & Hattenschwiler, ; Bílá et al., ; Chapman & Koch, ; Pérez Harguindeguy, Blundo, Gurvich, Díaz, & Cuevas, ; Wardle, Yeates, Barker, & Bonner, ), and identity or activity of decomposers (Handa et al., ; Schädler & Brandl, ; Vos, van Ruijven, Berg, Peeters, & Berendse, , ). Many of these studies showed that litter mixtures that are functionally dissimilar decompose synergistically, probably by providing complementary resources needed by generalist decomposers or by multiple specialist decomposers, which have complementary effects on decomposition (Bílá et al., ; Gessner et al., ; Meier & Bowman, ; Tardif & Shipley, ; Vos et al., ). But, other studies showed that trait dissimilarity might also render decomposition antagonistic as a given decomposer or detritivore might find its preferred resources diluted in unpreferred ones (Pan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…of decomposers (Handa et al, 2014;Schädler & Brandl, 2005;Vos, van Ruijven, Berg, Peeters, & Berendse, 2011. Many of these studies showed that litter mixtures that are functionally dissimilar decompose synergistically, probably by providing complementary resources needed by generalist decomposers or by multiple specialist decomposers, which have complementary effects on decomposition (Bílá et al, 2014;Gessner et al, 2010;Meier & Bowman, 2008;Tardif & Shipley, 2014;Vos et al, 2013). But, other studies showed that trait dissimilarity might also render decomposition antagonistic as a given decomposer or detritivore might find its preferred resources diluted in unpreferred ones (Pan et al, 2015).…”
mentioning
confidence: 99%
“…Low‐abundance species are assumed to contribute very little to the functioning of the systems they reside within. The mass–ratio hypothesis (Grime, ) predicts that a species' effect on ecosystem function is proportional to its relative abundance (Bílá et al., ). Numerous examples from plant (Grime, ; Ervin and Wetzel, ; Smith and Knapp, ), plankton (Dayton, ; Norberg, ), and animal (Dangles and Malmqvist, ; Balvanera et al., ; Larsen et al., ; Bílá et al., ; Cárdenas et al., ) communities demonstrate that dominant species shape ecosystem function.…”
mentioning
confidence: 99%
“…The mass–ratio hypothesis (Grime, ) predicts that a species' effect on ecosystem function is proportional to its relative abundance (Bílá et al., ). Numerous examples from plant (Grime, ; Ervin and Wetzel, ; Smith and Knapp, ), plankton (Dayton, ; Norberg, ), and animal (Dangles and Malmqvist, ; Balvanera et al., ; Larsen et al., ; Bílá et al., ; Cárdenas et al., ) communities demonstrate that dominant species shape ecosystem function. However, in many systems, low‐abundance (rare) species can exert large effects on ecosystem function (Zavaleta and Hulvey, ; Lyons et al., ; Hol et al., ; Hussa and Goodrich‐Blair, ; Mouillot et al., ; Mariotte, ; Ziegler et al., ).…”
mentioning
confidence: 99%